The Effect of Colchicine Concentration and Immersion Time on Growth and Morphological Characters of Acacia crassicarpa A. Cunn. Ex Benth In-vitro Explants - Frederika Sinuraya; Dewi Indriyani Roslim; Deviona Deviona; Suharyanto Suharyanto (Jurnal Biologi Tropis, 2023)
The production of polyploidy with a chemical mutagen such as colchicine is one strategy that can be applied to improve the genetic traits and wood properties of acacia trees. The aim of this study was to determine the effects of colchicine at various concentrations and immersion times on the percentage of surviving explants, percentage of rooted explants, and morphological traits of shoot and root A. crassicarpa in-vitro. A completely randomized design (CRD) with two factors was used in this study. The first factor was the concentration of colchicine solution with five levels (0,00%, 0,02%, 0,04%, 0,06%, and 0,08%), and the second factor was the immersion time with three levels (24, 48, and 72 hours). There were fifteen treatment combinations with each treatment repeated three times. Data were analyzed by ANOVA and Duncan’s multiple range test at 5% significance level. The results showed that the treatment combination of colchicine concentration with immersion time showed a significant effect on the percentage of surviving explants, number of leaves, number of shoots and height of A. crassicarpa explants, but did not significantly affect on the number of roots, length of the root and percentage of rooted A. crassicarpa explants.